2003
DOI: 10.1530/eje.0.1480505
|View full text |Cite
|
Sign up to set email alerts
|

Ret/PTC activation does not influence clinical and pathological features of adult papillary thyroid carcinomas

Abstract: Objective: RET proto-oncogene rearrangements (ret/PTCs) represent the most common genetic alterations found in papillary thyroid carcinomas (PTCs). Correlation of ret/PTC expression with clinical outcome is controversial. The aim of the present study was to analyze the frequency of RET rearrangements in adult PTCs, and to investigate if ret/PTCs influence biological behavior and clinical features of the cancers. Design: Ret/PTC rearrangements were looked for in tissue samples of 48 PTCs collected at our instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 28 publications
0
26
2
Order By: Relevance
“…In our series, we found a total of ten out of 40 (25%) BRAF WT PTC samples with broken RET above the cut-off level, a prevalence slightly lower than that reported in other Italian studies of comparable size, ranging from 27.5 to 35% (16,30,62,73,74).…”
Section: Discussioncontrasting
confidence: 75%
“…In our series, we found a total of ten out of 40 (25%) BRAF WT PTC samples with broken RET above the cut-off level, a prevalence slightly lower than that reported in other Italian studies of comparable size, ranging from 27.5 to 35% (16,30,62,73,74).…”
Section: Discussioncontrasting
confidence: 75%
“…Regarding RET/PTC, only a limited number of studies have evaluated its prognostic value. Some studies were unable to find any significant association between the presence of RET rearrangements and several clinical pathological features of aggressiveness (21,40,41). Few studies suggested that RET/PTC3 correlates with more advanced stage of disease (42,43) and aggressive variants such as solid (33) or tall-cell (44).…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis of the data published worldwide over a greater than 10-year period (Table 3) demonstrates an average prevalence of 18% for Southern blotting (67/370 cases tested, range 0-33%), [26][27][28][29][30][31] 15% for direct visualization of the RT-PCR amplicons (47/309 cases tested, range 4-45%) 7,32-35 and 48% for hybridization of blotted RT-PCR products (153/314 cases tested, range 0-85%). 4,[21][22][23][36][37][38][39] Allowing for the fact that Southern blotting permits the identification of all RET/PTC variants while the cases analyzed by RT-PCR listed above only screened the tumors for RET/PTC1, -2 and -3, there is a good correspondence between the sensitivity of Southern blotting and of direct gel visualization of RT-PCR products, as also demonstrated by parallel analysis of the same samples with the two methods. 44 When RT-PCR is followed by blotting of the amplicons and hybridization with RET-specific probes the sensitivity increases dramatically, by at least 100-fold according to some investigators.…”
Section: Discussionmentioning
confidence: 99%